Long‐Term Outcomes in Patients With Turner Syndrome: A 68‐Year Follow‐Up. Issue 11 (4th June 2019) - Fuchs, Margaret M.; Attenhofer Jost, Christine; Babovic‐Vuksanovic, Dusica; Connolly, Heidi M.; Egbe, Alexander
Abstract : Background: Turner syndrome (TS) is the most common sex chromosome abnormality in women and is associated with increased morbidity and mortality. We describe long‐term outcomes in a large cohort of patients with TS. Methods and Results: Retrospective review of patients with TS followed at Mayo Clinic Rochester from 1950 to 2017 was performed. Clinical, imaging, surgical, and genetic data were analyzed. Survival analysis was performed with the Kaplan–Meier method using age‐ and sex‐matched Olmsted County residents as the reference group. The study cohort comprised 317 patients with TS. Average age at diagnosis was 9 (range, 2–12) years, genetic testing was performed in 202 (64%), and pure monosomy X was present in 75 (37%). Congenital heart disease occurred in 131 (41%), with the most frequent lesions being bicuspid aortic valve (n=102, 32%) and coarctation of the aorta (n=43, 14%). Ascending aortic dilation was common, with mean aortic root size index 2 cm/m 2, and aortic dissection occurred in 6 (2%) patients. The average follow‐up was 11 (range, 2–26) years, yielding 3898 patient‐years, and during this period 46 (14%) patients died; mean age at the time of death was 53±17 years. Patients with TS had reduced survival compared with the control group (82% versus 94% at 30 years; P <0.001), and the leading causes of death were cardiovascular disease, liver disease, and malignancy. Conclusions: Patients with TS have reduced survival compared with age‐matched controls, and cardiovascular disease is the major cause of death. Further studies are required to determine if targeted cardiovascular risk factor modification will result in improved survival in this population.